The musketeers. The complete second season [videorecording (DVD)] - Burke, Tom, 1981-; Cabrera, Santiago; Charles, Howard, 1983-; Dowling, Alexandra, 1990-; Dumas, Alexandre, 1802-1870 (BBC Worldwide Americas, 2015)
Prepare for more pulse-pounding thrills, more breathtaking action and more high-stakes heroism. The gallivanting royal bodyguards for King Louis XIII, Athos, Aramis, Porthos and d'Artagnan, are back for love, honor and adventure. Together, the inseparable Musketeers employ their bravery and skill to track down a missing Musketeer; become embroiled in a full-scale riot orchestrated by a notorious criminal mastermind; and embark on a dangerous mission to Le Havre.